479 EVALUATION OF IRAQI MONTMORILLONITE AS ADSORBENT FOR THE REMOVAL OF OXYTETRACYCLINE FROM WATER - Barbooti, Mahmood; Al-Bassam, Khaldoon; Qasim, Bashar (Iraqi Journal of Science, 2024)
This work is a contribution to the global interest of scientific community in the field of cleaning the environment from drug and antibiotic residues which lead to the development of new generations of bacteria with improved resistance to antibiotics. The sorption of oxytetracyclin, OTC, on an Iraqi certified clay mineral, the montmorillonite, is used as indicative for the success of the used treatments. Batch equilibration experiments were carried out to follow the sorption behavior of OTC on the clay. The concentration of OTC was determined by spectral absorption at 360 nm which presented excellent correlation with high performance liquid chromatography, HPLC, method over a wide range of concentration (R2 = 0.977). After equilibration of synthetic OTC solutions with the clay for various intervals of time and various pH values, the concentration of OTC was employed to estimate the sorption efficiency of montmorillonite. The pH of the solution has only minor effect on the sorption efficiency. The kinetic treatment of the sorption results indicated two distinctive steps for the adsorption of OTC on the clay. Montmorillonite was proved as a candidate sorption material for OTC ensuring a removal efficiency of (94-96%) even at low clay contents. Experimentally the OTC concentration could be decreased from 0.5 to 0.03 mol/L at a pH value of 5.5 by sorption onto 2.0 g clay (montmorillonite)/L.